2011
DOI: 10.1891/1061-3749.19.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and Repeatability of an Infrared Thermometer

Abstract: Recently, manufacturers have devised thermometers for home use by patients, such as the TempTouch Infrared Thermometer (TTIR; Diabetica Solutions, San Antonio, TX), which is designed with a long handle that can be used for self-monitoring localized skin temperature of the feet and legs. This study assessed the level of agreement and repeatability of the TTIR compared to a thermistor-type thermometer (TT; PeriFlux, 5020 Temperature Unit, Perimed, Stockholm, Sweden), the reference standard. In 17 healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
0
21
1
Order By: Relevance
“…The manufacturer stated accuracy was ±0.2°C. This type of device has been adopted as a criterion during similar validity comparisons (Kelechi et al 2011;Buono et al 2007, Burnham et al 2006 were actively cooled using a large fan and cold drinks.…”
Section: Measurement Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer stated accuracy was ±0.2°C. This type of device has been adopted as a criterion during similar validity comparisons (Kelechi et al 2011;Buono et al 2007, Burnham et al 2006 were actively cooled using a large fan and cold drinks.…”
Section: Measurement Toolsmentioning
confidence: 99%
“…Typically, T SKIN has been measured using thermocouples or wired thermistors with recent literature adopting wired thermistors as the criterion measure when validating new tools (Kelechi et al 2011, Buono et al 2007, Burnham et al 2006. A thermocouple is a temperature-measuring device consisting of two dissimilar conductors that contact each other at one or more joint locations.…”
Section: Introductionmentioning
confidence: 99%
“…The clinically significant threshold for healthy normalised skin temperature differences is 0.5°C [ 23 , 24 ]. Consequently, mean differences between conductive and infrared devices measured at localised sites must not exceed this value [ 2 , 20 , 25 , 26 ]. However, no recommendations pertaining to the classification of practically meaningful differences and limits of agreement between conductive and infrared devices for the measurement of have been outlined.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline lower leg skin temperatures, measured 5 cm above the medial malleolus were recorded with the thermistor (PeriFlux 5020 Temperature Unit, Perimed, Stockholm, Sweden) which has previously been shown to demonstrate a high level of agreement with the infrared thermometer (TempTouch, Diabetica Solutions, San Antonio, TX) used in this study [7, 15]. Demographic data, vital signs, and the medical history were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have described skin temperature elevation and patterns of temperature variability of CVeD-inflamed skin, measured with validated infrared- and thermistor-type thermometers at the gaiter area of affected lower legs [7]. We found that skin temperature was elevated by ∼1-2°C compared to unaffected contralateral skin and the lower leg skin of healthy controls [8].…”
Section: Introductionmentioning
confidence: 98%